Early‐life stress leads to sex‐dependent changes in pubertal timing in rats that are reversed by a probiotic formulation. Issue 5 (24th July 2018) - Cowan, Caitlin S. M.; Richardson, Rick
Abstract: Puberty marks the beginning of a period of dramatic physical, hormonal, and social change. This instability has made adolescence infamous as a time of "storm and stress" and it is well‐established that stress during adolescence can be particularly damaging. However, prior stress may also shape the adolescent experience. In the present series of experiments, we observed sex‐specific effects of early‐life maternal separation stress on the timing of puberty onset in the rat. Specifically, stressed females exhibited earlier pubertal onset compared to standard‐reared females, whereas stressed males matured later than their standard‐reared counterparts. Further, we demonstrated that a probiotic treatment restores the normative timing of puberty onset in rodents of both sexes. These results are in keeping with previous findings that probiotics reverse stress‐induced changes in learned fear behaviors and stress hormone levels, highlighting the remarkable and wide‐ranging restorative effects of probiotics in the context of early‐life stress.